Palm vitamin E reduces locomotor dysfunction and morphological changes induced by spinal cord injury and protects against oxidative damage - Zadeh-Ardabili, P.M.; Rad, S.K.; Rad, S.K.; Khaza'ai, H.; Sanusi, J.; Zadeh, M.A.R.H. (Nature Publishing Group, 2017)
Spinal cord injury (SCI) occurs following different types of crushes. External and internal outcomes of SCI are including paralysis, cavity, and cyst formation. Effects of dietary derived antioxidants, such as palm vitamin E on central nervous system (CNS) encourage researchers to focus on the potential therapeutic benefits of antioxidant supplements. In the present study, experiments were carried out to evaluate the neuro-protective effect of the palm vitamin E on locomotor function and morphological damages induced SCI. Seventy-two male rats (Sprague-Dawley) were randomly divided into four groups: sham (laminectomy); control (supplemented with the palm vitamin E at a dose of 100 mg/kg/day); untreated-SCI (partial crush, 30-33% for 20 sec); treated-SCI (partial crush, 30-33% for 20 sec supplemented with the palm vitamin E at a dose of 100 mg/kg/day). The treatment with the palm vitamin E significantly improved the hind limb locomotor function, reduced the histopathological changes and the morphological damage in the spinal cord. Also, the palm vitamin E indicated a statistically significant decrease in the oxidative damage indicators, malondialdehyde (MDA) level and glutathione peroxidase (GPx) activity in the treated-SCI compared to the untreated-SCI.